Impaired Morris water task retention following T21 light dark cycle exposure is not due to reduced hippocampal c-FOS expression - Deibel, Scott H.; Higdon, S.; Cassell, T. T. S.; House-Denine, M. L.; Giberson, E.; Webb, I. C.; Thorpe, C. M. (Frontiers in Behavioral Neuroscience, 2022)
Circadian rhythms influence virtually all aspects of physiology and behaviour. This is problematic when circadian rhythms no longer reliably predict time. Circadian rhythm disruption can impair memory, yet we don’t know how this fully works at the systems and molecular level. When trying to determine the root of a memory impairment, assessing neuronal activation with c-FOS is useful. This has yet to be assessed in the hippocampi of circadian rhythm disrupted rats in a hippocampal gold standard task. Rats were trained on the Morris water task, then received six days of a 21-hour day (T21), 13 days of a normal light dark cycle, MWT probe trial, and tissue extraction an hour later. Despite having impaired memory in the probe trial, compared to controls there were no differences in c-FOS expression in hippocampal sub regions: CA1; CA3; Dentate gyrus. These data confirm others in hamsters demonstrating that arrhythmicity which produces an impairment in spontaneous alternation does not affect c-FOS in the dentate gyrus. The current study indicates that the memory impairment induced by a lighting manipulation is likely not due to attenuated neuronal activation. Determining how the master clock in the brain communicates with the hippocampus is needed to untangle the relationship between circadian rhythms and memory.